Are We Winning the Fight against Poverty? An Assessment of the Poverty Situation in the Philippines - Aubrey D. Tabuga; Christian D. Mina; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2010)
In 2006, poverty incidence in the Philippines went up by 3 percentage points from 2003, marking a reversal against the downward trend in previous poverty estimates. This upward trend went against expectations after the Philippine economy exhibited a relatively robust performance during this period. The reasons as to why this has happened are explored in this paper. Meanwhile, income inequality measures do not show significant change over the years. Natural disasters and economic crises further add to the already difficult work of reducing poverty. The MDG deadline looms ahead and time is running out in the country's battle against poverty. In this report, the poverty situation is again revisited and closely examined. It aims to assess whether the country has made any improvements or not and to answer several key questions such as: What should likely be the focus of poverty reduction efforts? Why is it that poverty rose despite the relatively fast economic growth in recent years? What can we learn from this experience?
Keywords: 330; poverty; Philippines; income inequality; decomposition of poverty; Armut; Armutsbekämpfung; Wirkungsanalyse; Philippinen